Fossil fruits of Illigera (Hernandiaceae) from the Eocene of central Tibetan Plateau. Issue 6 (11th January 2021) - Wang, Teng‐Xiang; Del Rio, Cédric; Manchester, Steven R.; Liu, Jia; Wu, Fei‐Xiang; Deng, Wei‐Yu‐Dong; Su, Tao; Zhou, Zhe‐Kun
Abstract: Illigera (Hernandiaceae) is a liana genus distributed mainly in the tropical Asia and Africa. Previous fossil records suggested that Illigera was restricted in western North America during the Eocene. Recent paleobotanical investigation has unveiled a Paleogene flora that is totally different from today's vegetation in central Tibet. This provides novel insights into the paleoenvironmental change during the evolution of the Tibetan Plateau (TP). Here, we investigated 10 fruit impressions of Illigera from the early middle Eocene Niubao Formation in the Bangor Basin, central TP. The fossil winged fruits are characterized by their eroded fruit wings, well preserved fusiform locular areas with a median ridge bisecting the fruit, and short veins fanning radially outward. These features allow us to assign these fossils to Illigera eocenica, a species originally discovered in the Eocene of western North America. This is the second fossil occurrence of Illigera worldwide, and the first in Asia. Our finding suggests a warm and humid climate in the central TP during the early middle Eocene, and a close floristic link between Asia and North America during the Paleogene. We also propose a Northern Hemisphere origin and a Paleogene dispersal event from Northern Hemisphere to Africa for Illigera . Abstract : New Illigera fossil fruits from the Eocene Tibetan Plateau reveal floristic links between Asia and other parts of world.